Salt-tolerant alternative crops as sources of quality food to mitigate the negative impact of salinity on agricultural production - Egea, Isabel; Estrada, Yanira; Faura, Celia; Egea-Fernández, José M.; Bolarin, Maria C.; Flores, Francisco B. (Frontiers in Plant Science, 2023)
An increase of abiotic stress tolerance and nutritive value of foods is currently a priority because of climate change and rising world population. Among abiotic stresses, salt stress is one of the main problems in agriculture. Mounting urbanization and industrialization, and increasing global food demand, are pressing farmers to make use of marginal lands affected by salinity and low-quality saline water. In that situation, one of the most promising approaches is searching for new sources of genetic variation like salt-tolerant alternative crops or underexploited crops. They are generally less efficient than cultivated crops in optimal conditions due to lower yield but represent an alternative in stressful growth conditions. In this review, we summarize the advances achieved in research on underexploited species differing in their genetic nature. First, we highlight advances in research on salt tolerance of traditional varieties of tomato or landraces; varieties selected and developed by smallholder farmers for adaptation to their local environments showing specific attractive fruit quality traits. We remark advances attained in screening a collection of tomato traditional varieties gathered in Spanish Southeast, a very productive region which environment is extremely stressing. Second, we explore the opportunities of exploiting the natural variation of halophytes, in particular quinoa and amaranth. The adaptation of both species in stressful growth conditions is becoming an increasingly important issue, especially for their cultivation in arid and semiarid areas prone to be affected by salinity. Here we present a project developed in Spanish Southeast, where quinoa and amaranth varieties are being adapted for their culture under abiotic stress targeting high quality grain.